5G Network Security Issues, Challenges, Opportunities and Future Directions: A Survey. Issue 1 (August 2021) - Humayun, Mamoona; Hamid, Bushra; Jhanjhi, NZ; Suseendran, G.; Talib, M N
Abstract: 5G is expected to bring tremendous advancement in wireless cellular network by providing faster speed, high capacity and low latency. It has widely been adopted in various parts of the world and is expected to bring a noteworthy revolution in major industries and overall economies. Although 5G service providers are promising integrity, confidentiality and availability of data, still security is an important concern that needs to be addressed. This paper provides a detailed survey on 5G security by addressing 5G opportunities, common threats targeting 5G network along with their mitigation strategies, security services offered by 5G networks and 5G security challenges. We have also provided a case study to demonstrate the potentials of 5G. This survey will help 5G researchers, service providers and 5G users in getting quick awareness of 5G network.